Pengembangan Asesmen Berbasis Google Classroom pada Mata Pelajaran Instalasi Penerangan Listrik - Farel Akbar Hatama; Hansi Effendi (Jurnal Pendidikan Teknik Elektro, 2022)
There are 2 objectives of the research, namely the first to develop an assessment using Google Classroom for the subject of electrical lighting installation for class XI TITL at SMK Negeri 5 Padang and the second, namely to determine the feasibility of a Google Classroom-based assessment in terms of validity and practicality. This type of research is research and development with a 4-D model consisting of 4 stages, namely the definition stage, the design stage, the development stage, and the dissemination stage. The subject of this research is a Google Classroom-based assessment on the subject of Electrical Lighting Installation. This data collection uses a validation sheet given to one lecturer in the Department of Electrical Engineering, Faculty of Engineering, State University of Padang and two teachers of Electrical Lighting Installation subjects at SMK Negeri 5 Padang. Practical data using a questionnaire given to three teachers of Electrical Lighting Installation subjects and twenty students of class XI TITL. Based on the research, data obtained with a validity level of 86.7% for the very valid category and a practicality level of 87.8% for the very practical category. Thus this research has resulted in a Google Classroom-based assessment on the subject of Electrical Lighting Installation which is valid and practical.